Perceived work environment and employee engagement among manufacturing employees - Kanapathy, Gengatharan (2021)
Employee engagement has emerged as an important management focused activity in order to perform in a dynamic business environment. Engaged employees are expected to be able to help organizations in all sectors including manufacturing to achieve its business objectives. This study, in general, aims to explore the factors that may be relevant to employee engagement. In specific, this study attempts to examine the relationships between perceived of work environment (the work itself, relationship with co-workers, leadership of supervisor, pay and benefit) and employee engagement among manufacturing employees in Sendayan Tech Valley. Quantitative method was used whereby questionnaires were provided to participants. Data acquired was examined using the Statistical Package for Social Science (SPSS) software. Inferential analyses specifically regression and correlation were used to examine the relationship between perceived of work environment factors and employee engagement. The findings of this study showed that, of four factors analysed, only the work itself had significant relationship with employee engagement whereas relationship with co-workers, leadership of supervisor, pay and benefit did not show any significant relationships with employee engagement. The results derived from this study suggest that the work itself should be given attention if the management of these manufacturing companies were to increase the engagement of their employees. This study was carried out on two manufacturing companies using convenience sampling technique, therefore the results cannot be generalized to other manufacturing companies or other organizations in different sectors. Future research is hope to extend the current scope of the research to include more manufacturing companies throughout the country and utilize a different sampling technique to confirm on these findings.